A method for preparing microgel-reinforced nanocellulose-based porous material
By preparing nano -cellulose micro -gels and using Pickering emulsion template technology and the cross -linking reaction of aldehydescel cellulose, a micro -gel with a three -dimensional network skeleton enhances nanocytopenic pores, which solves existing cellulose bases The problem of insufficient porous material strength achieves higher compression strength and structural reinforcement effects.
Patent Information
- Application Number
- CN202310299127.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-03-24
AI Technical Summary
The strength of existing cellulose-based porous materials is easily affected by the pore structure and pore distribution, and the compression strength generally does not exceed 0.6MPa, making it difficult to meet the needs of practical applications.
By preparing nanocytulose micro -gels, and using Pickering emulsion template technology and aldehyde -based nanocyllic cross -linking reactions to form a micro -gel with a three -dimensional network skeleton enhanced nanocytopromal -based pores.
The structure and mechanical properties of nano -cellulose -based pores are significantly improved. The compression strength can reach 0.725MPa or higher, suitable for adsorption, gas sensing and other fields.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing functional porous materials, and in particular is a method for preparing a microgel-reinforced nano-cellulose-based porous material. Background Art
[0002] Porous materials have the advantages of high specific surface area, thermal insulation, and good permeability due to their unique structure, and are widely used in packaging, food, chemical industry and other fields. Porous materials prepared from biomass are renewable and biodegradable, and are gradually gaining attention. Among them, cellulose-based porous materials combine the advantages of cellulose being rich in hydroxyl groups, biodegradable and biocompatible, as well as the characteristics of porous materials such as ultra-lightweight, high porosity, high specific area and pore size distribution. They are widely used in adsorption, gas sensing and other fields, but the strength of cellulose-based porous materials is easily affected by the pore structure and pore distribution.
[0003] At present, there are many reports on the preparation methods of cellulose-based porous materials, and commonly used methods include freeze drying, supercritical drying and Pickering emulsion template method. For example, in the technical scheme of Chinese Patent Application Publication No. CN108484965A, cellulose and cellulose derivatives are mixed to form a suspension and then freeze-dried to obtain a cellulose porous material. In the technical scheme of Chinese Patent Application Publication No. CN112552553A, the Pickering emulsion template method is adopted, nanocellulose is used to stabilize paraffin emulsion droplets and emulsify to obtain a Pickering emulsion, and then freeze-drying and in-situ polymerization are used to prepare a cellulose-based foam porous material. However, the strength of the porous materials obtained by these methods is easily affected by the strength of the network structure itself formed by overlapping the cellulose fibers as the skeleton, and the compressive strength of the material is generally not more than 0.6MPa, which has great limitations for practical applications.
[0004] Therefore, the mechanical properties of nanocellulose porous materials need to be further enhanced. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a microgel-reinforced nano-cellulose-based porous material, which can effectively enhance the structure and mechanical properties of the nano-cellulose-based porous material.
[0006] The present invention solves the above technical problems with the following technical solutions:
[0007] The preparation method of the microgel-enhanced nanocellulose-based porous material of the present invention comprises the following steps:
[0008] (1) Preparation of nanocellulose microgel: Nanocellulose is dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 1.0% to 3.0%; a 2.0% polyethyleneimine aqueous solution is added dropwise on the nanocellulose aqueous dispersion in an equal volume ratio, and the mixture is allowed to stand at room temperature for 24 hours to obtain a gel matrix; the gel matrix is transferred to a 2.0% polyethyleneimine aqueous solution, soaked and aged for 12 hours, and then taken out and soaked in an EDC / NHS mixed solution for reaction for 24 hours to obtain a nanocellulose hydrogel; the hydrogel is then rinsed twice with an equal mass ratio of deionized water, and then an equal mass ratio of deionized water is added to the mixture and treated at a mechanical shear rate of 10,000 rpm for 3 minutes to obtain a nanocellulose microgel;
[0009] (2) Preparing a Pickering emulsion: adding n-hexane dropwise to the nanocellulose microgel prepared in step (1), stirring and mixing at 3000 rpm to obtain a Pickering emulsion; wherein the nanocellulose microgel and n-hexane are used in a weight ratio of 10 to 30 parts: 70 to 90 parts;
[0010] (3) preparing an emulsion gel: adding an aldehyde-based nanocellulose aqueous dispersion having a mass concentration of 1.0% to 3.0% to the Pickering emulsion obtained in step (2), stirring and mixing, standing for 24 hours, and then curing to obtain an emulsion gel, wherein the Pickering emulsion and the aldehyde-based nanocellulose aqueous dispersion are used in a weight ratio of 10 to 30 parts: 70 to 90 parts;
[0011] (4) Preparation of porous material: The emulsion gel obtained in step (3) was placed in a fume hood and dried at room temperature for 24 hours to evaporate the n-hexane, then frozen at -18°C for 24 hours, and then moved to a freeze dryer with a cold trap temperature of -65°C and a vacuum degree of 1 Pa and dried for 48 hours to obtain a microgel-reinforced nanocellulose-based porous material.
[0012] In the step (1), the surface carboxyl content of the nanocellulose is 1.0 to 1.4 mmol / g, and the molecular weight of the polyethyleneimine in the polyethyleneimine aqueous solution is 10 kDa to 70 kDa.
[0013] In the step (1), the mass ratio of EDC to NHS in the EDC / NHS mixed solution is 1.5 to 2.5:1.
[0014] In the step (3), the surface aldehyde content of the aldehyde nanocellulose is 1.0 to 3.0 mmol / g.
[0015] The present invention introduces a micron-scale pore structure based on the Pickering emulsion template technology, and uses the carboxyl groups on the nanocellulose and the amino groups on the polyethyleneimine to undergo an amidation reaction to form a gel network to prepare a nanocellulose microgel. The nanocellulose microgel is used as an emulsifier for the Pickering emulsion, and the prepared water-in-oil type emulsion has high stability and high internal phase advantages. After the nanocellulose microgel in the Pickering emulsion is mixed with the aldehyde-based nanocellulose, the amino groups on the microgel can be cross-linked and solidified with the aldehyde groups on the aldehyde-based nanocellulose to obtain an emulsion gel. After the emulsion gel is volatilized to remove the oil phase, it can be directly freeze-dried to obtain a microgel-enhanced nanocellulose-based porous material. At the same time, the nanocellulose microgel particles contain dynamic covalent bonds. During the emulsion drying process, the microgel particles on the oil-water interface and the residual microgel particles in the water phase are cross-linked to form a three-dimensional network skeleton, which plays a role in strengthening the structure and mechanical properties of the nanocellulose-based porous material.
[0016] Compared with the prior art, the method of the present invention has the following beneficial effects:
[0017] 1) The present invention is based on Pickering emulsion template technology and utilizes the interfacial stability and cross-linking reactivity of nanocellulose microgels to make the structure and morphology of the pores controllable, thereby obtaining nanocellulose-based porous materials with enhanced structure and mechanical properties, which have important application value in the fields of adsorption, gas sensing, and controlled release of functional substances.
[0018] 2) The present invention utilizes nanocellulose microgel as an emulsifier for Pickering emulsion. The microgel has excellent interfacial properties, which is conducive to obtaining a high-stability high-internal phase emulsion, and is conducive to controlling the size of pores and maintaining their shape during the preparation of porous materials by the emulsion template method.
[0019] 3) The present invention uses aldehyde-based nanocellulose as a cross-linking curing agent of Pickering emulsion to prepare emulsion gel based on Schiff base reaction. During the drying process of the emulsion gel, the three-dimensional network skeleton of the nanocellulose contains dynamic covalent bonds, which can strengthen the structure and performance of the nanocellulose-based porous material. DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The chemical reagents and raw materials used in the following examples are all of analytical grade.
[0021] Example 1
[0022] A method for preparing a microgel-reinforced nanocellulose-based porous material comprises the following steps:
[0023] (1) Preparation of nanocellulose microgel: Nanocellulose with a surface carboxyl content of 1.0 mmol / g is dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 1.0%; a polyethyleneimine aqueous solution with a mass concentration of 2.0% is added dropwise on the nanocellulose aqueous dispersion in an equal volume ratio, and the mixture is allowed to stand at room temperature for 24 hours to obtain a gel matrix; the gel matrix is transferred to a polyethyleneimine aqueous solution with a mass concentration of 2.0% and soaked for aging for 12 hours, then taken out and soaked in an EDC / NHS mixed solution (the mass ratio of EDC to NHS is 2.0:1) for reaction for 24 hours to obtain a nanocellulose hydrogel; the hydrogel is rinsed twice with deionized water of an equal mass ratio, and then deionized water of an equal mass ratio is added and treated at a mechanical shear rate of 10,000 rpm for 3 minutes to obtain a nanocellulose microgel, wherein the polyethyleneimine molecular weight is 10 kDa;
[0024] (2) Preparing a Pickering emulsion: adding n-hexane dropwise to the nanocellulose microgel prepared in step (1), stirring and mixing at 3000 rpm to obtain a Pickering emulsion; wherein the nanocellulose microgel and n-hexane are used in a weight ratio of 20 parts:80 parts;
[0025] (3) preparing an emulsion gel: adding an aldehyde-based nanocellulose aqueous dispersion to the Pickering emulsion obtained in step (2), stirring and mixing, standing for 24 hours, and curing to obtain an emulsion gel, wherein the Pickering emulsion and the aldehyde-based nanocellulose aqueous dispersion are used in a weight ratio of 30 parts:70 parts, the aldehyde content on the surface of the aldehyde-based nanocellulose is 1.0 mmol / g, and the mass concentration of the aldehyde-based nanocellulose aqueous dispersion is 3.0%;
[0026] (4) Preparation of porous material: The emulsion gel obtained in step (3) was placed in a fume hood and dried at room temperature for 24 hours to evaporate the n-hexane, then frozen at -18°C for 24 hours, and then moved to a freeze dryer with a cold trap temperature of -65°C and a vacuum degree of 1 Pa and dried for 48 hours to obtain a microgel-reinforced nanocellulose-based porous material.
[0027] The density of the microgel-enhanced nanocellulose-based porous material prepared in this example is 4.8 mg / cm 3 The porosity is 99.825%, and the compression strength is 0.725MPa as determined by compression test.
[0028] Example 2
[0029] A method for preparing a microgel-reinforced nanocellulose-based porous material comprises the following steps:
[0030] (1) Preparation of nanocellulose microgel: Nanocellulose with a surface carboxyl content of 1.2 mmol / g is dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 2.0%; a polyethyleneimine aqueous solution with a mass concentration of 2.0% is added dropwise on the nanocellulose aqueous dispersion in an equal volume ratio, and the mixture is allowed to stand at room temperature for 24 hours to obtain a gel matrix; the gel matrix is transferred to a polyethyleneimine aqueous solution with a mass concentration of 2.0% and soaked for aging for 12 hours, then taken out and soaked in an EDC / NHS mixed solution (the mass ratio of EDC to NHS is 2.0:1) for reaction for 24 hours to obtain a nanocellulose hydrogel; the hydrogel is rinsed twice with deionized water of an equal mass ratio, and then deionized water of an equal mass ratio is added and treated at a mechanical shear rate of 10,000 rpm for 3 minutes to obtain a nanocellulose microgel, wherein the polyethyleneimine molecular weight is 70 kDa;
[0031] (2) Preparing a Pickering emulsion: adding n-hexane dropwise to the nanocellulose microgel prepared in step (1), stirring and mixing at 3000 rpm to obtain a Pickering emulsion; wherein the nanocellulose microgel and n-hexane are used in a weight ratio of 10 parts:90 parts;
[0032] (3) preparing an emulsion gel: adding an aldehyde-based nanocellulose aqueous dispersion to the Pickering emulsion obtained in step (2), stirring and mixing, and curing the mixture after standing for 24 hours to obtain an emulsion gel, wherein the amount of the Pickering emulsion to the aldehyde-based nanocellulose aqueous dispersion is 20 parts by weight: 80 parts by weight, the aldehyde content of the aldehyde-based nanocellulose surface is 3.0 mmol / g, and the mass concentration of the aldehyde-based nanocellulose aqueous dispersion is 2.0%;
[0033] (4) Preparation of porous material: The emulsion gel obtained in step (3) was placed in a fume hood and dried at room temperature for 24 hours to evaporate the n-hexane, then frozen at -18°C for 24 hours, and then moved to a freeze dryer with a cold trap temperature of -65°C and a vacuum degree of 1 Pa and dried for 48 hours to obtain a microgel-reinforced nanocellulose-based porous material.
[0034] The density of the microgel-enhanced nanocellulose-based porous material prepared in this example is 5.6 mg / cm 3 The porosity is 99.882%, and the compression strength is 0.794MPa as determined by compression test.
[0035] Example 3
[0036] A method for preparing a microgel-reinforced nanocellulose-based porous material comprises the following steps:
[0037] (1) Preparation of nanocellulose microgel: Nanocellulose with a surface carboxyl content of 1.4 mmol / g was dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 3.0%; a 2.0% polyethyleneimine aqueous solution was added dropwise on the nanocellulose aqueous dispersion in an equal volume ratio, and the mixture was allowed to stand at room temperature for 24 hours to obtain a gel matrix; the gel matrix was transferred to a 2.0% polyethyleneimine aqueous solution, immersed and aged for 12 hours, and then taken out and immersed in an EDC / NHS mixed solution (the mass ratio of EDC to NHS was 1.5:1) for reaction for 24 hours to obtain a nanocellulose hydrogel; the hydrogel was rinsed twice with an equal mass ratio of deionized water, and then an equal mass ratio of deionized water was added and treated at a mechanical shear rate of 10,000 rpm for 3 minutes to obtain a nanocellulose microgel, wherein the polyethyleneimine molecular weight was 40 kDa;
[0038] (2) Preparing a Pickering emulsion: adding n-hexane dropwise to the nanocellulose microgel prepared in step (1), stirring and mixing at 3000 rpm to obtain a Pickering emulsion; wherein the nanocellulose microgel and n-hexane are used in a weight ratio of 30 parts:70 parts;
[0039] (3) preparing an emulsion gel: adding an aldehyde-based nanocellulose aqueous dispersion to the Pickering emulsion obtained in step (2), stirring and mixing, standing for 24 hours, and curing to obtain an emulsion gel, wherein the amount of the Pickering emulsion and the aldehyde-based nanocellulose aqueous dispersion is 10 parts by weight: 90 parts by weight, the aldehyde content of the aldehyde-based nanocellulose surface is 2.0 mmol / g, and the mass concentration of the aldehyde-based nanocellulose aqueous dispersion is 1.0%;
[0040] (4) Preparation of porous material: The emulsion gel obtained in step (3) was placed in a fume hood and dried at room temperature for 24 hours to evaporate the n-hexane, then frozen at -18°C for 24 hours, and then moved to a freeze dryer with a cold trap temperature of -65°C and a vacuum degree of 1 Pa and dried for 48 hours to obtain a microgel-reinforced nanocellulose-based porous material.
[0041] The density of the microgel-enhanced nanocellulose-based porous material prepared in this example is 6.7 mg / cm 3 The porosity is 99.754%, and the compression strength is 0.856MPa as determined by compression test.
Claims
1. A method for preparing a microgel-enhanced nanocellulose-based porous material, characterized in that: The steps are as follows: (1) Preparation of nanocellulose microgel: Nanocellulose with a surface carboxyl content of 1.0 to 1.4 mmol / g is dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 1.0% to 3.0%; a 2.0% polyethyleneimine aqueous solution is added dropwise on top of the nanocellulose aqueous dispersion in an equal volume ratio, and the mixture is allowed to stand at room temperature for 24 h to obtain a gel matrix; the gel matrix is transferred to a 2.0% polyethyleneimine aqueous solution and immersed in it for aging for 12 h, then taken out and immersed in an EDC / NHS mixed solution for reaction for 24 h to obtain a nanocellulose hydrogel; the hydrogel is then rinsed twice with an equal mass ratio of deionized water, and then an equal mass ratio of deionized water is added to the mixture and treated at a mechanical shear rate of 10,000 rpm for 3 min to obtain a nanocellulose microgel; (2) Preparing a Pickering emulsion: adding n-hexane dropwise to the nanocellulose microgel prepared in step (1), stirring and mixing at 3000 rpm to obtain a Pickering emulsion; wherein the nanocellulose microgel and n-hexane are used in a weight ratio of 10 to 30 parts: 70 to 90 parts; (3) preparing an emulsion gel: adding an aldehyde-based nanocellulose aqueous dispersion having a mass concentration of 1.0% to 3.0% to the Pickering emulsion prepared in step (2), stirring and mixing the mixture evenly, standing the mixture for 24 hours, and then curing the mixture to obtain an emulsion gel, wherein the weight ratio of the Pickering emulsion to the aldehyde-based nanocellulose aqueous dispersion is 10 to 30 parts: 70 to 90 parts; (4) Preparation of porous material: The emulsion gel prepared in step (3) was placed in a fume hood and dried at room temperature for 24 hours to evaporate the n-hexane, then frozen at -18°C for 24 hours, and then moved to a freeze dryer with a cold trap temperature of -65°C and a vacuum degree of 1 Pa and dried for 48 hours to obtain a microgel-reinforced nanocellulose-based porous material.
2. The method for preparing the microgel-enhanced nanocellulose-based porous material according to claim 1, characterized in that: In step (1), the molecular weight of polyethyleneimine in the polyethyleneimine aqueous solution is 10 kDa to 70 kDa.
3. The method for preparing the microgel-enhanced nanocellulose-based porous material according to claim 1, characterized in that: In step (1), the mass ratio of EDC to NHS in the EDC / NHS mixed solution is 1.5 to 2.5:
1.
4. The method for preparing the microgel-enhanced nanocellulose-based porous material according to claim 1, characterized in that: In step (3), the surface aldehyde content of the aldehyde nanocellulose is 1.0 to 3.0 mmol / g.
Citation Information
Patent Citations
Preparation method and application of cellulose porous material
CN108484965A
Composite foam porous material as well as preparation method and application thereof
CN112552553A
Polyethyleneimine based chloramines type antibacterial cellulose membrane, preparation method and application
CN109232953A
Amino functionalized porous material and preparation method and application thereof
CN109621918A